Sistem Informasi Pengolahan Data Barang Dan Service Komputer Pada Toko Sinar Terang Komputer Pacitan - Sukmana, Fendra; Purnama, Bambang Eka; ., Sukadi (Speed - Indonesian Journal on Computer Science, 2014)
Abstract: During the data processing goods and service computer shop computer Sinar Terang Pacitan done conventionally , in this case the data recording of goods and service computers still use the big books . Sometimes part of the sale of goods difficulties in data processing , report generation data items and service computers . so the manual recording of data that have been made can be lost at any time and take a long time in searching data and computer service transactions. Information systems data processing goods and service computers are created using Visual Basic as the primary interface maker and Microsoft Office Access as its database . This program allows the user to input the data , edit data , delete data , data retrieval , and data printing to paper media . The data entered in the form of classification of goods , the goods data , supplier data , the data type of the goods , the data type of service , sales data items , the data entry service . While the output is in the form of information system reports the stock of goods , goods sales reports , purchasing reports , service data reports and memoranda of the sale of goods and service memorandum. Information systems data processing goods and service computers may be one solution that can be used to facilitate the sale of data processing and computer services that accelerate reporting stock of goods , sales reports , purchase reports , computer service reports and memorandum items the sale of goods and memorandum computer service transactions . Keywords : Information systems of data processing goods and service Abstraksi : Selama ini pengolahan data barang dan service komputer pada toko Sinar Terang komputer Pacitan di lakukan secara konvensional, dalam hal ini pencatatan data barang dan service komputer masih mengunakan pembukuan besar. Terkadang bagian penjualan kesulitan dalam pengolahan data barang, pembuatan laporan data barang dan service komputer . sehingga pencatatan manual data-data yang telah di buat sewaktu-waktu dapat hilang dan membutuhkan waktu yang lama dalam pencarian data barang dan transaksi service computer. Sistem informasi pengolahan data barang dan service komputer ini dibuat dengan menggunakan Visual Basic NET sebagai pembuat interface utama dan Microsoft Office Acces sebagai basis datanya. Program ini memungkinkan user untuk input data, edit data, hapus data, pencarian data, dan pencetakan data ke media kertas. Data yang diinputkan berupa klasifikasi barang, data barang, data supplier, data jenis barang,data jenis service, data penjualan barang, data service masuk. Sedangkan output yang dihasilkan sistem informasi ini berupa laporan stock barang, laporan penjualan barang, laporan pembelian, laporan data service dan nota transaksi penjualan barang dan nota service. Sistem informasi pengolahan data barang dan service komputer ini dapat menjadi salah satu solusi yang dapat digunakan untuk mempermudah dalam mengolah data penjualan barang, dan service komputer sehingga mempercepatÂ  membuat laporan stock barang, laporan penjualan,laporan pembelian , laporan service komputer barang serta nota transaksi penjualan barang dan nota transaksi service komputer. Kata kunci : Sistem Informasi pengolahan data barang dan service